Navigating English Writing Proficiency Tests in the Era of Artificial Intelligence - Benni Ichsanda Rahman Hz; Rebecca Evelyn Laiya; Martiman Suazisiwa Sarumaha; Supiyandi (UNIB Press, 2023)
The establishment and growth of artificial intelligence (AI) technology has sparked tremendous interest in the field of writing skills, as AI writing tools have the potential to assist humans in creating and refining text. The availability of these tools may lead to a reliance on AI in writing, which raises concerns about the potential degradation of writing skills. To that extent, will the writing skill session in English proficiency tests (e.g: TOEFL, IELTS, PTE Academic, TOEIC) be displaced? Utilizing a phenomenological case study, the researcher interviews four experienced test administrators in North Sumatera, Indonesia, to explore their perspective regarding to the impact of AI writing tools on the applications of writing tests in English proficiency tests. Various insightful perspectives are elaborated by the participants, implicating the future of English writing proficiency tests in the age of AI. However, in case this study is conducted in Indonesia and only involves four test administrators, a wider scale of research is needed to further investigate the potential impact of AI writing tools on writing skills across various contexts and languages.